Influence of Regional Original Income, General Allocation Funds, Special Allocation Funds and Profit Sharing Funds Regional Shopping (Case Study of 29 Districts in East Java Province) - Fitri Handayani; Suwandi; Indrian Supheni; Wiwin Alief Bachtiar (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
The aim of this research is to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds and Profit Sharing Funds on Regional Expenditures, the research method uses quantitative methods with secondary data in the form of Regional Revenue and Expenditure Budget Realization reports, the analytical method in this research is analysis multiple linear regression with the help of SPSS Version 21. With a total sample of 29 districts with an observation period of 4 years, namely 2018-2021, so the total sample used in this research is 116 data. The results of the study show that partially the Regional Original Income, General Allocation Funds and Profit Sharing Funds have a positive effect while Special Allocation Funds have no effect on Regional Expenditures. Simultaneous test results of the dependent variable have a positive effect on Regional Expenditures.